(untitled) (Research, Society and Development, 2023)
To analyze how superbug infections are established in the operating room and in the intensive care unit. This article is an integrative literature review. The databases of scientific articles were used to perform the searches: US National Library of Medicine (PubMed) and Scientific Electronic Library Online (SciELO) Latin American and Caribbean Literature in Health Sciences (LILACS) and Virtual Health Library (BVS). The key words were used to meet the theme, CRI and ND, with a prospective design: "infection" AND "surgical center" AND "intensive care unit". The time frame includes articles published between 2010 and 2022. The hospital environment is highly potentiated for the development of superbugs in patients who underwent surgical procedures. In addition to care during surgery, it is necessary to assess how external factors influence the proliferation of these bacterial microorganisms. It is necessary to evaluate the sterile conditions of the hospital environment, preoperative and postoperative preparations, in addition, studies indicate that the patient’s lifestyle habits, such as alcohol consumption and nicotine use, influence in the greater probability of developing infections. Another relevant factor is the patient’s history of previous illnesses , because if you have an immunosuppressed immune system, there is a greater chance of developing contamination by superbugs. Bacterial contamination still has a high prevalence worldwide, becoming a public health problem.